Perbedaan Fungsi Ventrikel Kanan pada Pasien Hipertensi Arteri Pulmonal Akibat Penyakit Jantung Bawaan dan Tanpa Penyakit Jantung Bawaan - Fatimah Azzahra; Mefri Yanni; Erlina Rustam; Noverika Windasari; Shinta Ayu Intan (Fakultas Kedokteran Universitas Riau, 2026)
Pulmonary arterial hypertension (PAH) leads to right ventricular (RV) dysfunction due to chronic volume overload in congenital heart disease (CHD) or pressure overload in isolated PAH. This study aimed to evaluate differences in RV function between PAH patients with and without CHD, given their distinct pathophysiological mechanisms. A cross-sectional analytical study was conducted using medical records from Dr. M. Djamil Padang Hospital (2023–2024), including 54 patients (27 per group) selected via consecutive sampling. Bivariate analysis using the Chi-square test was employed to compare standard echocardiographic parameters: three-dimensional ejection fraction (3DEF), tricuspid annular plane systolic excursion (TAPSE), fractional area change (FAC), S', and RV Strain. The results revealed no significant differences in RV function parameters between the two groups: 3DEF (p=0.773), TAPSE (p=0.293), FAC (p=0.224), S' (p=1.000), and RV Strain (p=0.559). Furthermore, median values for 3DEF, TAPSE, FAC, and S' were within normal limits, whereas mean RV Strain values were in the abnormal range for both study groups. In conclusion, despite the differing underlying pathophysiologies, there is no significant difference in right ventricular function between patients with PAH due to CHD and those without CHD.